MAPK signaling regulates c-MYC for melanoma cell adaptation to asparagine restriction - Pathria, Gaurav; Verma, Sachin; Yin, Jun; Scott, David A; Ronai, Ze’ev A (EMBO reports, 2021)
Amino acid restriction is among promising potential cancer treatment strategies. However, cancer cells employ a multitude of mechanisms to mount resistance to amino acid restriction, which impede the latter’s clinical development. Here we show that MAPK signaling activation in asparagine-restricted melanoma cells impairs GSK3-β-mediated c-MYC degradation. In turn, elevated c-MYC supports ATF4 translational induction by enhancing the expression of the amino acid transporter SLC7A5, increasing the uptake of essential amino acids, and the subsequent maintenance of mTORC1 activity in asparagine-restricted melanoma cells. Blocking the MAPK-c-MYC-SLC7A5 signaling axis cooperates with asparagine restriction to effectively suppress melanoma cell proliferation. This work reveals a previously unknown axis of cancer cell adaptation to asparagine restriction and informs mechanisms that may be targeted for enhanced therapeutic efficacy of asparagine limiting strategies. SYNOPSIS This study demonstrates that blocking MAPK cooperates with asparagine restriction to effectively suppress melanoma cell proliferation. MAPK activation impairs GSK3-β mediated c-MYC degradation in asparagine-restricted melanoma cells. c-MYC promotes SLC7A5 expression to increase the uptake of essential amino acids. Essential amino acids induce mTORC1 activity, supporting ATF4 translation. Blocking the MAPK-c-MYC-SLC7A5-mTORC1 signaling axis cooperates with asparagine restriction to restrict melanoma cell proliferation. Graphical Abstract This study demonstrates that blocking MAPK cooperates with asparagine restriction to effectively suppress melanoma cell proliferation.